'Uphi?'1 ICTs and the mitigation of distance in a South African township. (August 2015) - Powell, Crystal
Abstract: Langa Township, located in Cape Town, South Africa is home to many internal South African migrants and external African immigrants. As a mobile population, many Langa residents have embraced the mobile phone as a means of securing relationships with family members living elsewhere, while also maintaining relationships forged within the township and South Africa in general. Addressing the role of technology in a historical perspective, this article addresses the various ways that mobile phones have both mitigated and exacerbated distance for residents while also acknowledging the advantages and disadvantages of mobile phones for different generations of migrants in the township. Highlights: Mobile phones have greatly impacted South Africans. Mobile phones play an essential role in the lives of migrants and other mobile bodies. For older residents, adapting to the use of mobile phones has been difficult but necessary. Mobile phones are crucial for sharing information, maintaining close ties with 'home', and securing remittances. Mobile phones both exacerbate and mitigate distance.